Redefining the high‐grade B cell lymphoma with double/triple rearrangements of MYC and BCL2/BCL6 genes. Learning from a case report. Issue 1 (9th November 2021) - Rodríguez‐Pinilla, Socorro María; Salgado, Rocío Nieves; Chamizo, Cristina; Santonja, Carlos; Stewart, Peter; Carvajal, Nerea; McCafferty, Neil; Manso, Rebeca; Morillo, Daniel; Piris, Miguel Ángel; González de Castro, David
Abstract: We report a patient initially diagnosed with a triple hit high‐grade B cell lymphoma (HGBL‐TH), in which further morphologic, immunohistochemical, and next‐generation sequencing studies of subsequent specimens disclosed it to be a germinal center diffuse large B cell lymphoma (GC‐DLBCL) with BCL2/BCL6 gene translocations, PVT1 ‐deletion, and gain of MYC genes evolving from a previous follicular lymphoma. However, fluorescence in situ hybridization (FISH) studies with the break‐apart probe for MYC gene showed a fusion and two separated signals (red and green, respectively) leading to the interpretation of MYC gene translocation and a false diagnosis of a TH‐lymphoma, according to the recent WHO classification. Nevertheless, PVT1 deletion plus MYC gain/amplification has been described as a cause of the double‐hi transcription profile. These data highlight the need for new criteria to identify these highly aggressive lymphomas.